Injection Laryngoplasty Using Micronized Acellular Dermis for Vocal Fold Paralysis: Long-term Voice Outcomes. (May 2016) - Hernandez, Stephen C.; Sibley, Haley; Fink, Daniel S.; Kunduk, Melda; Schexnaildre, Mell; Kakade, Anagha; McWhorter, Andrew J.
Objectives: Micronized acellular dermis has been used for nearly 15 years to correct glottic insufficiency. With previous demonstration of safety and efficacy, this study aims to evaluate intermediate and long-term voice outcomes in those who underwent injection laryngoplasty for unilateral vocal fold paralysis. Technique and timing of injection were also reviewed to assess their impact on outcomes. Study Design: Case series with chart review. Setting: Tertiary care center. Subjects and Methods: Patients undergoing injection laryngoplasty from May 2007 to September 2012 were reviewed for possible inclusion. Pre- and postoperative Voice Handicap Index (VHI) scores, as well as senior speech-language pathologists' blinded assessment of voice, were collected for analysis. The final sample included patients who underwent injection laryngoplasty for unilateral vocal fold paralysis, 33 of whom had VHI results and 37 of whom had voice recordings. Additional data were obtained, including technique and timing of injection. Results: Analysis was performed on those patients above with VHI and perceptual voice grades before and at least 6 months following injection. Mean VHI improved by 28.7 points at 6 to 12 months and 22.8 points at >12 months ( P = .001). Mean perceptual voice grades improved by 17.6 points at 6 to 12 months and 16.3 points at >12 months ( P < .001). No statistically significant difference was found with technique or time to injection. Conclusion: Micronized acellular dermis is a safe injectable that improved both patient-completed voice ratings and blinded reviewer voice gradings at intermediate and long-term follow-up. Further investigation may be warranted regarding technique and timing of injection.